2006
DOI: 10.1111/j.1365-2672.2006.02827.x
|View full text |Cite
|
Sign up to set email alerts
|

A newly developed assay to study the minimum inhibitory concentration of Satureja spinosa essential oil

Abstract: Aims:  The minimum inhibitory concentration (MIC) of Satureja spinosa essential oil against Staphylococcus aureus, Escherichia coli O157:H7, Listeria monocytogenes, Salmonella enterica, Salmonella serovar Enteritidis PT4 and Bacillus cereus was comparatively assessed with an established optical density method as well as a novel impedimetric method. Methods and Results:  The impedimetric analysis takes into account information of microbial growth, such as detection time, maximum conductance, and slope of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 40 publications
2
49
0
Order By: Relevance
“…For each bacteria density we fit the positive droplet fraction data by the Gompertz function 23,24 . Then we calculate the MIC as the antibiotic concentration value where Gompertz fit crosses the 0.5 viability fraction in droplets ( Fig 2G).…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…For each bacteria density we fit the positive droplet fraction data by the Gompertz function 23,24 . Then we calculate the MIC as the antibiotic concentration value where Gompertz fit crosses the 0.5 viability fraction in droplets ( Fig 2G).…”
Section: Main Textmentioning
confidence: 99%
“…1C from the main text: the normalized fraction almost always decreases with the antibiotic concentration. For each bacterial density we fit the data by the Gompertz function 23,24 , which is a 2-parameter function:…”
Section: Mic Calculationmentioning
confidence: 99%
“…The regression analysis was performed by using the Generalised Reduced Gradient algorithm (Excel solver) and the least squares optimisation where the objective function is expressed as a sum of squares. The minimum inhibitory concentration (MIC), defined as the concentration above which no growth is observed relative to the control and the non-inhibitory concentration (NIC) defined as the concentration below which normal visible growth is observed (Chorianopoulos et al 2006), were estimated from the LPM as follows (Chorianopoulos et al 2006; Guiller et al 2007): …”
Section: Calculation (Quantitative Assessment Of the Inhibitory Concementioning
confidence: 99%
“…(2008). Some studies have reported using two inoculation levels (Chorianopoulos et al. 2006; Santiesteban‐López et al.…”
Section: Introductionmentioning
confidence: 99%